The Invention of Authorship in Early Modern Japan: Theorizing Commercial Creativity in the Fiction of Miyako no Nishiki. - Atherton, David C. (Journal of Japanese Studies)
The article from the Journal of Japanese Studies explores the concept of authorship and creativity in early modern Japan, focusing on the commercial writer Miyako no Nishiki. It discusses how the emergence of the author as a figure of popular interest was influenced by the commercial print market and the relationships between writers, publishers, and readers. The text delves into the complexities of authorship, plagiarism, and the evolving nature of the publishing industry during the turn of the eighteenth century in Japan. Through an analysis of Miyako no Nishiki's works, the article highlights the author's self-referential and meta-commentative approach to writing, shedding light on the dynamic relationship between authors, texts, and readers in the context of commercial fiction.